Legal Issues Regarding The Granting Of Conditional Release To Foreign Prisoners In Fulfilling Legal Certainty (Case Study At Class I Tanjung Gusta Medan Correctional Institution) - Ramawinda, Beby Fitria; Marlina, Marlina; Rizky, Fajar Khaify (Ilmu Hukum Prima (IHP), 2025)
Parole is a crucial component of the correctional system that aims to reduce prison overcrowding while ensuring legal certainty for inmates. However, the implementation of parole for foreign inmates in Indonesia faces significant administrative and inter-agency coordination challenges. This gap between legal provisions and practical implementation creates obstacles, especially for foreign inmates who face a more complex legal status and cumbersome bureaucratic procedures. This study aims to analyze the implementation of parole for foreign inmates to fulfill legal certainty at the Tanjung Gusta Class I Correctional Institution in Medan. Using an empirical juridical method with a qualitative approach, this study involved document analysis, interviews with prison officers, and direct field observations. The research findings revealed that the parole process for foreign inmates is hampered by complex bureaucracy, a lack of understanding among officers and the public, and inadequate coordination between correctional institutions, immigration authorities, and other related institutions. In addition, unintegrated administrative procedures cause delays in granting the right to parole. This study concludes that improving inter-agency coordination, simplifying administrative procedures, and strengthening outreach efforts to officers and the public are crucial to realizing legal certainty for foreign inmates. These efforts are expected to support the correctional system's goal of rehabilitation. and social reintegration of prisoners while effectively addressing prison overcrowding issues.